2023
DOI: 10.2147/ceor.s397766
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Willingness to Pay for Social Health Insurance and Its Determinant Factors at Harar Region, Ethiopia, 2021

Abstract: Background: Most developing nations lag behind in maintaining their populations' health. These nations are characterized by underfinancing, low health cost protection mechanisms for the poor, and lack of risk pooling and cost sharing methods. To tackle this challenge, Ethiopia proposed social health insurance in 2010 even though its implementation was delayed. Hence, the purpose of this study was to assess teachers' willingness to pay for the newly proposed social health insurance and its associated factors. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…For instance, in Mekelle, the largest city in the country's Tigray region, a majority (85%) of the 381 public servants were willing to be part of the social health insurance scheme, with a mean WTP of 3.6% of their monthly salary [18]. Although not as high as in Mekelle, surveys amongst teachers in Harar, Wolaita Sodo, Gondar and Akaki Kality (a sub-city of Addis Ababa), yielded WTP rates of between 62% and 74% [19][20][21][22]. A meta-analysis covering 18 studies showed that, on average, about 42% of formal sector workers are WTP for SHI [23].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in Mekelle, the largest city in the country's Tigray region, a majority (85%) of the 381 public servants were willing to be part of the social health insurance scheme, with a mean WTP of 3.6% of their monthly salary [18]. Although not as high as in Mekelle, surveys amongst teachers in Harar, Wolaita Sodo, Gondar and Akaki Kality (a sub-city of Addis Ababa), yielded WTP rates of between 62% and 74% [19][20][21][22]. A meta-analysis covering 18 studies showed that, on average, about 42% of formal sector workers are WTP for SHI [23].…”
Section: Introductionmentioning
confidence: 99%